2022
DOI: 10.1111/apt.17216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastrointestinal landmarks using the gas‐sensing capsule and wireless motility capsule

Abstract: Background: Accurate definition of the gastroduodenal and ileocaecal junctions (GDJ, ICJ) is essential for the measurement of regional transit times. Aims:To compare the assessment of these landmarks using the novel gas-sensing capsule and validated wireless motility capsule (WMC), and to evaluate intra-subject variance in transit times Methods: Healthy subjects ingested the gas-sensing capsule and WMC tandemly in random order. Inter-observer agreement was evaluated by intra-class correlation coefficient (ICC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Colonic transit time was calculated from the time each capsule reached the ileocaecal junction to its excretion, as previously reported and validated 22,23 . Colonic pH was examined as an average across the entire colon, together with nadir and peak pH and their timing after the ileocaecal valve.…”
Section: Methodsmentioning
confidence: 99%
“…Colonic transit time was calculated from the time each capsule reached the ileocaecal junction to its excretion, as previously reported and validated 22,23 . Colonic pH was examined as an average across the entire colon, together with nadir and peak pH and their timing after the ileocaecal valve.…”
Section: Methodsmentioning
confidence: 99%
“…Thwaites et al reported the development of an investigational gas‐sensing capsule to inform gastrointestinal transit times based on differences in regional production of luminal gas contents. Their report provides prospective comparative data between the gas‐sensing capsule and WMC in healthy subjects in support of construct validity for this novel technology 4 . This clinical trial provides insight on a novel mechanism of measuring luminal gas production to assess regional gastrointestinal transit, in contrast to WMC technology that measures transit primarily by pH.…”
mentioning
confidence: 87%
“…Their report provides prospective comparative data between the gassensing capsule and WMC in healthy subjects in support of construct validity for this novel technology. 4 This clinical trial provides insight on a novel mechanism of measuring luminal gas production to assess regional gastrointestinal transit, in contrast to WMC technology that measures transit primarily by pH. This work is part of broader efforts in the gastroenterology community to reinvigorate the technology pipeline, recognising that WMC was originally FDAcleared over 15 years ago.…”
mentioning
confidence: 99%
“…Sensing technologies such as optical sensing, [26] gas sensing, [27][28][29] pH sensing, [30] temperature sensing, [31] and electrochemical impedance spectroscopy (EIS) [32] have been readily integrated into ingestible capsules in recent years. These sensing modalities can give insights into the current state of inflammation in the GI tract and be used to inform active targeted drug delivery to afflicted tissue locations.…”
mentioning
confidence: 99%